Prolonged Distress in Residents Exposed to a Technological Disaster - (:unkn) unknown (My University, 2020)
This study investigated the prolonged emotional and behavioral effects of an ongoing technolog-ical disaster, the Flint Water Crisis. Past research indicates that surviving a technological disaster may have prolonged effects, including stress related disorders, even after the initial exposure pe-riod has passed. The survey consisted of questions involving knowledge of the effects of lead and Legionnaires’ disease as well as questions regarding how to use water filters properly, ques-tions modeled after the Health Belief Model, behavioral changes, and an anxiety, stress, and de-pression scale. Additionally, there were questions asking participants how well they feel the crisis was handled, how much control they feel they have, how comfortable they are using tap water, and if they feel the crisis is over. Data was analyzed using a series of ANOVAs and regressions where applicable. Results showed that residents of Flint have higher emotional levels and that Health Belief Model scores may play an important role in predicting knowledge scores. These results indicate that a mental health intervention may still be needed due to the prolonged elevat-ed stress, anxiety, and depression levels of Flint residents.
Keywords: Anxiety; Flint Water Crisis; Health Belief Model; Stress; Technological Disasters